Clinical characteristic analysis of 25 cases of hepatic portal venous gas - Ji, Changhui; Zhang, Lihong; Cheng, Zhirong; Jiang, Zhilong; Ji, Tao; Ye, Bo (Frontiers in Surgery, 2025)
ObjectiveTo analyze the clinical characteristics, etiological distribution, and treatment outcomes of Hepatic Portal Venous Gas (HPVG) in a cohort of elderly patients with multiple comorbidities, and to evaluate the impact of early surgical intervention on survival rates.MethodsA retrospective study was conducted on 25 patients with HPVG admitted to Taixing People's Hospital of Yangzhou University from January 2010 to June 2024. The study included demographic characteristics, symptoms, comorbidities, etiology, laboratory and abdominal CT results, treatment, and outcomes.ResultsThe male-to-female ratio was 2.6:1, with a median age of 62 years. Common symptoms included abdominal pain (88%), vomiting (44%), and septic shock (36%). Comorbidities included coronary heart disease (52%), type 2 diabetes (64%), and hypertension (76%). Leukocytosis was observed in 84% of patients. Abdominal CT scans revealed HPVG in all patients. Etiologies included intestinal ischemia/necrosis (56%), intestinal obstruction (24%), suspected intestinal perforation (12%), and intestinal inflammation (8%). Treatment involved emergency surgery combined with antibiotic therapy in 72% of patients and conservative management in 28%. Outcomes showed 60% effectiveness and 40% mortality. Among the surgical group, 12 patients recovered and 6 died; among the conservative group, 3 recovered and 4 died.ConclusionHPVG has complex etiologies, and abdominal CT is the recommended diagnostic method. Patients with acute abdomen should undergo surgery as soon as possible to improve prognosis, although some cases have poor prognosis.